The Effect of Leadership on Employee Loyalty and Organizational Trust As Mediation Variables - Untung La Paudi; I Ketut R Sudiarditha; Usep Suhud (CV. Syntax Corporation Indonesia, 2022)
Leadership is an important factor in an organization's work in keeping the organization running to achieve its goals. In an effort to increase employee loyalty, every organization needs to test the level of organizational trust. This study aims to determine the effect of leadership on employee loyalty, and organizational trust as a mediating variable. The sample in this research is all employees in the regional secretariat office of Wakatobi Regency. The sample in this study used convenience sampling with a total sample of 250. The data analysis method used in this study was structural equation modeling (SEM) using Amos version 24. The results of this study indicate that leadership has a negative effect on employee loyalty on the probability value of the test results which are above 5% 0.805 and the critical ratio (CR) test results -0.247. shows that leadership has a positive effect on organizational trust, the probability value of the test results is (0%) and the critical ratio (CR) is 7.964. shows that organizational trust has a positive effect on employee loyalty on the probability value of (0%) and the critical ratio (CR) of 5.896. the mediation variable above shows that there is an indirect variable influence with a coefficient of 0.05 and the estimated standard inderct effect value of 0.867